How China Escaped the Poverty Trap - Ang, Yuen Yuen (Cornell University Press, 2016)
Before markets opened in 1978, China was an impoverished planned econo my governed by a Maoist bureaucracy. In just three decades it evolved into the world's second-largest economy and is today guided by highly entrepreneurial bureaucrats. In How China Escaped the Poverty Trap, Yu en Yuen Ang explains this astonishing metamorphosis. Rather than insis t that either strong institutions of good governance foster markets or that growth enables good governance, Ang lays out a new, dynamic fram ework for understanding development broadly. Successful development, s he contends, is a coevolutionary process in which markets and governme nts mutually adapt.By mapping this coevolution, Ang reveals a startlin g conclusion: poor and weak countries can escape the poverty trap by f irst harnessing weak institutions—features that defy norms of good gov ernance—to build markets. Further, she stresses that adaptive processe s, though essential for development, do not automatically occur. Highl ighting three universal roadblocks to adaptation, Ang identifies how C hinese reformers crafted enabling conditions for effective improvisati on.How China Escaped the Poverty Trap offers the most complete synthes is to date of the numerous interacting forces that have shaped China’s dramatic makeover and the problems it faces today. Looking beyond Chi na, Ang also traces the coevolutionary sequence of development in late medieval Europe, antebellum United States, and contemporary Nigeria, and finds surprising parallels among these otherwise disparate cases. Indispensable to all who care about development, this groundbreaking b ook challenges the convention of linear thinking and points to an alte rnative path out of poverty traps.
Keywords: IMPORTANT